2021
DOI: 10.1002/ncp.10637
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Malnutrition Clinical Characteristics in Critically Ill Patients

Abstract: Background: This study aimed to validate the Malnutrition Clinical Characteristics (MCC) compared with the Subjective Global Assessment (SGA), considering anthropometric measures, comorbidities, and mortality in critically ill patients. Methods: This longitudinal observational study included patients admitted to the general intensive care unit (ICU) of a public hospital. SGA was used as the reference standard for diagnosing malnutrition. The inclusion criteria were patients receiving nutrition support therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
(115 reference statements)
1
12
0
5
Order By: Relevance
“…Our findings reinforce the PNI as a feasible tool associated with hospital length of stay, although other factors may have contributed to the lack of statistical significance in the other models analyzed here. In line with the Vavruk et al ( 1 ), malnourished patients admitted to the ICU evaluated using SGA had significantly higher mortality rates and longer hospital length of stay compared to well-nourished patients. Likewise, the association of oxygen therapy requirement with the reduced potential to discharge reach statistical significance in the unadjusted and adjusted Cox regression model and time-dependent covariate Cox regression model, suggesting the prognostic effect of the oxygen therapy requirement as a predictor of hospital length of stay in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our findings reinforce the PNI as a feasible tool associated with hospital length of stay, although other factors may have contributed to the lack of statistical significance in the other models analyzed here. In line with the Vavruk et al ( 1 ), malnourished patients admitted to the ICU evaluated using SGA had significantly higher mortality rates and longer hospital length of stay compared to well-nourished patients. Likewise, the association of oxygen therapy requirement with the reduced potential to discharge reach statistical significance in the unadjusted and adjusted Cox regression model and time-dependent covariate Cox regression model, suggesting the prognostic effect of the oxygen therapy requirement as a predictor of hospital length of stay in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 70%
“…Nutritional assessment emerges as an indispensable management at hospital admission because malnourished patients imply a significantly longer hospital length of stay and high mortality rates ( 1 ). Regarding coronavirus disease 2019 (COVID-19), the results have been similar.…”
Section: Introductionmentioning
confidence: 99%
“…MNA is a reliable tool and has been validated for older adults (≥65 years) in clinics, hospitals, and long‐term care settings 15,16,18 . Emerging data are beginning to highlight that the Academy/ASPEN approach may be able to predict adverse outcomes and diagnose malnutrition; however, significantly more study in multiple populations that compares the approach to a “gold standard” such as SGA is required for this approach to be considered valid 24–31 . Guidance for the review of GLIM validation studies, as outlined by Keller et al, will be valuable for evaluating such studies as they are published 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies evaluating the AACCs have been published, 22 30 and a large, multisite validation study is underway 21 . A recent review that included five studies 22–26 using the AACCs in adults found that those diagnosed with malnutrition through this tool had longer hospital lengths of stay, higher odds of readmission within 30 days of discharge, and higher odds of mortality 27 …”
Section: Academy/aspen Malnutrition Consensus Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation